Short-sightedness in Youth Welfare Provision: The Case of RSA in France - Juliana Bidadanure (Intergenerational Justice Review)
This paper reconstitutes and addresses critically the deontological and consequentialist arguments given by the French government to justify the denial of the national guaranteed minimum income support (RSA) to young people under 25 years old. The deontological arguments express a concern for distributive justice and suggest that young people do not deserve income support. The consequentialist arguments, on the other hand, emphasise social eﬃciency: they draw on the alleged negative outcomes that the extension of income support to young people would bring about. After analysing each argument, this paper concludes that the denial of RSA to young people is an illegitimate discrimination. It then proposes that we understand our duties towards young people through an account of prudence that reconciles both (1) concerns of distributive justice with concerns for social eﬃciency and (2) concerns for inter- and intragenerational justices.